2009
DOI: 10.11646/zootaxa.2273.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Catalog of the New World Biting Midges North of Mexico (Diptera: Ceratopogonidae)

Abstract: This catalog of the biting midges (Diptera: Ceratopogonidae) of the New World north of Mexico includes 603 species and 39 genera. The full citation, province or state of the type locality and distribution by province and/or state of each species is given. The most recent revision for each genus, subgenus and species group is cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
136
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 1 publication
0
136
0
5
Order By: Relevance
“…The description of B. laneae and the collection of B. woodruffi in Florida increases the number of Brachypogon species in the Nearctic from six to eight and the number of species in the subgenus Brachypogon from two to four (Borkent and Grogan 2009). Additional field collections and detailed taxonomic study of museum material from North America is needed for this genus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The description of B. laneae and the collection of B. woodruffi in Florida increases the number of Brachypogon species in the Nearctic from six to eight and the number of species in the subgenus Brachypogon from two to four (Borkent and Grogan 2009). Additional field collections and detailed taxonomic study of museum material from North America is needed for this genus.…”
Section: Discussionmentioning
confidence: 99%
“…The family Ceratopogonidae (Diptera) is species rich, with 6,056 extant, nominal species worldwide (Borkent 2011), including 603 in America north of Mexico (Borkent and Grogan 2009). Members of the genus Brachypogon Kieffer (Ceratopogonidae: Ceratopogoninae: Ceratopogonini) are small midges that are predaceous on other small nematocerous flies (Downes 1978; as species of Ceratopogon).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Culicoides riouxi was treated as a synonym of Culicoides reconditus in Borkent and Wirth (1997) but restored from synonymy in Borkent (2012). Delecolle et al (1983) reported Culicoides riouxi as a valid species from Finland (N: Tvärminne).…”
Section: Notesmentioning
confidence: 99%
“…The Ceratopogonidae (biting midges) are generally small flies with a nearly worldwide distribution; the family includes 6,180 extant species in 111 genera (Borkent 2014a) but undoubtedly, many more undescribed species await discovery. Immatures are found in a wide array of aquatic, semiaquatic and moist terrestrial habitats.…”
Section: Introductionmentioning
confidence: 99%